2024
DOI: 10.3390/life14020163
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Extracellular Vesicles in SARS-CoV-2-Induced Acute Kidney Injury: An Overview

Carter Bernal,
Christiane How-Volkman,
Madison Spencer
et al.

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has affected millions worldwide since its outbreak in the winter of 2019. While extensive research has primarily focused on the deleterious respiratory effects of SARS-CoV-2 in recent years, its pan-tropism has become evident. Among the vital organs susceptible to SARS-CoV-2 infection is the kidney. Post SARS-CoV-2 infection, patients have developed coronavirus disease 19 (COVID-19), with reported incidences of COVID-19 patients developing acute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 118 publications
(136 reference statements)
0
1
0
Order By: Relevance
“…These EVs can transfer viral components like CD9 and ACE2, aiding in virus docking and entry into cells. Studies have shown that EVs can carry many virus particles, contributing to the transmission of SARS-CoV-2 [73][74][75]. Furthermore, EVs released from SARS-CoV-2infected cells are involved in reprogramming the proteome and transcriptome of host cells, promoting the viral life cycle, and sustaining infection.…”
Section: Vaccination With Nanoparticles (Lnp) and Extracellular Vesic...mentioning
confidence: 99%
“…These EVs can transfer viral components like CD9 and ACE2, aiding in virus docking and entry into cells. Studies have shown that EVs can carry many virus particles, contributing to the transmission of SARS-CoV-2 [73][74][75]. Furthermore, EVs released from SARS-CoV-2infected cells are involved in reprogramming the proteome and transcriptome of host cells, promoting the viral life cycle, and sustaining infection.…”
Section: Vaccination With Nanoparticles (Lnp) and Extracellular Vesic...mentioning
confidence: 99%